The Effect of Brand Image and Promotion on Purchase Decision on Air Asia - Aswanti Setyawati; Ichwandi Irsyad Podungge; Farrell Aljamael Danantyo (Green Publisher, 2025)
The tight competition in the aviation industry, especially in airlines that implement the low-cost concept (LCC), and the impact of COVID-19 require airline companies or LCC airlines to adapt by making relevant strategic adjustments to remain competitive amid intense competition in LCC airlines. This study aims to determine the effect of brand image and promotion on purchasing decisions for Air Asia Airlines. The research method used is quantitative, using a variance-based Structural Equation Model (SEM) analysis tool with the help of the SmartPLS 4.0 system. The population of this study consisted of all users of Air Asia airline services on the CGK-SIN route, with a sample of 100 respondents. Non-probability sampling techniques were used to determine sample criteria by convenience sampling. The study's results show a significant positive influence between Brand Image and Promotion on Purchasing Decisions for Air Asia Airlines tickets.